Magnitude and gender-specific circumstances of depression among elderly population residing in an Urban slum area of a City in Maharashtra: A mixed-method study - Barsha Gadapani Pathak; Swati Deshpande; Rukman M Manapurath (Wolters Kluwer Medknow Publications, 2020)
The burden of geriatric mental health in India is showing a silent epidemic trend, but the knowledge on spectrum of their mental well-being dwelling in slums is very trivial. This mixed-method study aimed to estimate the proportion of depression among elderly and to find out the gender-specific circumstances, leading to depression. A total of 209 subjects selected through multistage sampling from an urban slum in a city of Maharashtra were interviewed for estimating depression, and six focus group discussions (FGDs) were conducted to explore the circumstances. Overall, 42.1% of elderly people had depression with 2.8% severe depression. Major themes highlighted after FGDs were self-esteem, social role, dependence, negative experience, and disgrace among males, and among females, main themes were justifiable reason, managing mood, suppression, undesirable events, and stigma. Depression is a significant public health problem, and a diverse approach is required to understand the perception of elderlies which will highlight the core issues related to depression.